Development of a Novel Phenotypic Roadmap to Improve Blueberry Quality and Storability - Farneti, Brian; Emanuelli, Francesco; Khomenko, Iuliia; Ajelli, Matteo; Biasioli, Franco; Giongo, Lara (Frontiers in Plant Science, 2020)
Improved fruit quality and prolonged storage attitude are key breeding traits for blueberry (Vaccinium spp.) fruit. However, until now, breeding selection was mostly oriented on the amelioration of agronomic traits, such as flowering time, chilling requirement or plant structure, ignoring the possible storage effect on fruit quality. Since consumers identify flavour and sweetness as positive blueberry quality traits, and texture attributes such as mealy and pasty as negative ones, the development of objective and reliable methodologies for texture and flavour profiling are essential both at harvest and during fruit storage. This study aimed to estimate the potential genetic variability among blueberry cultivars for both VOCs and texture traits, by Proton Transfer Reaction- Time of Flight- Mass Spectrometry (PTR-ToF-MS) and a texture analyzer respectively, taking into consideration the influence of prolonged storage. The exploitation of the genetic variability existing within the investigated blueberry germplasm collection (including both southern, northern, hybrids and rabbiteyes) allowed a precise identification of the best performing cultivars to be used as superior parental lines for future breeding programs. This comprehensive characterization of blueberry aroma allowed the identification of a wide pull of spectrometric features, mostly related to aldehydes, alcohols, terpenoids, and esters, that can be used as putative biomarkers to rapidly evaluate the blueberry aroma variations related to genetic differences and storability. This study introduces a phenotyping protocol to support breeding selection and quality control within the entire blueberry production chain.